Improving vocational students’ learning outcomes through problem-based learning with multimodal learning media - Dwi Fitria Al Husaeni; Eka Fitrajaya Rahman; Budi Mulyanti; Amay Suherman; Ade Gafar Abdullah; Lala Septem Riza; Erna Piantari; Sabila Fauziyya; Eki Nugraha (Universitas Pendidikan Indonesia, 2025)
Learning in vocational schools, particularly in database subjects, is still hampered by conventional methods that do not develop critical thinking skills and practical applications that meet industry needs. This study aims to assess the effect of using learning media in implementing the Problem-Based Learning (PBL) model on improving vocational students' learning outcomes, particularly in database materials. The research employed a three-cycle Classroom Action Research (CAR) method, conducted with 32 students of class XI RPL at SMKN 13 Bandung. The learning strategy in this study was designed using a PBL approach and integrated multimodal media, including PDF modules, PowerPoint presentations, and learning videos. The results showed a significant and consistent increase in student learning outcomes, with the average score rising from 66.30 in the first cycle to 81.84 in the third cycle. This finding confirms that the use of varied learning media in PBL can enhance conceptual understanding and increase students' active engagement in learning. Abstrak Pembelajaran di SMK, khususnya pada mata pelajaran basis data masih terkendala oleh metode konvensional yang kurang mengembangkan keterampilan berpikir kritis dan penerapan praktis sesuai kebutuhan industri. Penelitian ini bertujuan untuk mengukur pengaruh penggunaan media pembelajaran dalam penerapan model Problem-Based Learning (PBL) terhadap peningkatan hasil belajar siswa SMK, khususnya pada materi basis data. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) tiga siklus, yang dilaksanakan terhadap 32 siswa kelas XI RPL di SMKN 13 Bandung. Strategi pembelajaran dalam penelitian ini dirancang dengan pendekatan PBL yang diintegrasikan dengan media pembelajaran multimoda yang terdiri dari modul PDF, presentasi PowerPoint, dan video pembelajaran. Hasil penelitian menunjukkan peningkatan hasil belajar siswa yang signifikan dan stabil, dengan skor rata-rata meningkat dari 66,30 pada siklus I menjadi 81,84 pada siklus III. Temuan ini menegaskan bahwa penggunaan media pembelajaran yang bervariasi dalam konteks PBL dapat mendorong pemahaman konseptual yang lebih baik dan meningkatkan keterlibatan aktif siswa dalam pembelajaran. Kata Kunci: media pembelajaran; pembelajaran berbasis masalah; sekolah menengah kejuruan